The Acceptance Of E-Learning As A Corporate Training Tool : A Case Study On Maxis Communications Berhad - Govindasamay, Sreeratha S. (2004)
This paper focuses on the acceptance of Cyber Train as the corporate training tool in Maxis. Although it has been introduced for almost four years now, nostudy has been conducted to explore if Cyber Train has been accepted and used effectively by its employees. This study will lead find out if Cyber Train has been accepted as a corporate learning tool and if it needs any improvement.